Behaviour of upstream migrating adult salmon (Salmo salar L.) in the tailrace channels of hydropeaking hydropower plants. (19th August 2019) - Vehanen, Teppo; Louhi, Pauliina; Huusko, Ari; Mäki‐Petäys, Aki; van der Meer, Olli; Orell, Panu; Huusko, Riina; Jaukkuri, Mikko; Sutela, Tapio
Abstract: In hydropeaking rivers, flow regulation typically follows demands in electricity consumption. One hundred and twenty one adult salmon were tagged with radio transmitters to study their spawning run migration patterns in hydropeaking conditions. The fish were released in small groups into the rivers Kemijoki and Iijoki, in Finland. Typically, salmon made subsequent up‐ and downstream movements ascending upstream to the tailrace of the power station and then descending again downstream to lower water velocities. The rate of these migration attempts was higher in mid‐summer and at relatively high flows. On an hourly basis, the pattern of migration attempts followed a trend of increasing attempts at dawn and higher discharges and a decreasing trend towards dusk and low flows. It was concluded that day length and discharge were the most important environmental factors, while temperature had less effect on the pattern of migration attempts.